Penerapan Metode Direct Instruction dengan Guided Practice dalam Pelatihan Pemanfaatan LMS untuk Pembelajaran Hybrid - Aulia, Indra; Farah Afianti; Ari Moesriami Barmawi; Audrey Kurvanka; Rafi Athallah Sjakha; Muhammad Azwar Zulmi; Juri Febrianto; Muhammad Raihan Fadani (Jurnal Pengabdian Kepada Masyarakat, 2025)
The digital transformation in vocational education demands institutions to optimize the use of Learning Management Systems (LMS) as effective platforms for hybrid learning. Politeknik Penerbangan Indonesia Curug has adopted LMS, yet its usage remains limited to administrative functions and lacks deeper pedagogical integration. This community service initiative aimed to enhance the digital competencies of teaching staff through intensive LMS training based on the Direct Instruction with Guided Practice method. The program's partner consisted of lecturers from PPI Curug. The training was conducted in stages, including material delivery via Telkom University's e-learning platform, interactive offline workshops, guided hands-on sessions, evaluation through pre- and post-tests, and final feedback. Results showed an average score increase of 7.47 points, with 93.3% of participants achieving post-test scores within the 91–100 range. This effort aligns with Indonesia’s Asta Cita vision, particularly Asta Cita 4, in strengthening human resources, science, and technology towards realizing Indonesia Emas 2045. It also supports the Sustainable Development Goals (SDG) point 4 on Quality Education through the digitalization of learning processes. Consequently, this activity reflects the strong commitment of Telkom University’s academic community in upholding the values of HEI (Harmony, Excellence, Integrity), which derive from the AKHLAK BUMN core values, serving as the foundation of institutional culture and service. Through structured collaboration, this program contributes to building an innovative and sustainable digital education ecosystem.